2022
DOI: 10.1051/0004-6361/202243947
|View full text |Cite
|
Sign up to set email alerts
|

Stirring the base of the solar wind: On heat transfer and vortex formation

Abstract: Context. Current models of the solar wind must approximate (or ignore) the small-scale dynamics within the solar atmosphere, however these are likely important in shaping the emerging wave-turbulence spectrum and ultimately heating/accelerating the coronal plasma.Aims. This study strives to make connections between small-scale vortex motions at the base of the solar wind and the resulting heating/acceleration of coronal plasma. Methods. The Bifrost code produces realistic simulations of the solar atmosphere th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 159 publications
2
7
0
Order By: Relevance
“…The merged MC exhibits a longer lifetime of 1650 s (20,460 s < t < 22,110 s) in comparison to the average lifetime of individual MCs, which is typically 300-500 s. This finding is consistent with prior observations demonstrating that the lifetimes of magnetic bright points (MBPs), which serve as observational signatures of MCs, are prolonged during merging events as compared to the lifetimes of individual MBPs (Keys et al 2011). Given that MCs can impede local magnetoconvection and prevent the collapse of photospheric vortices (Finley et al 2022), it is plausible that the prolonged lifetimes of MCs observed in this study may facilitate the development of long-lived photospheric vortices, which can, in turn, give rise to magnetic tornadoes featuring the large-scale chromospheric swirls. The detailed analysis of the condition for magnetic tornadoes to form is a line for future research.…”
Section: Efficient Energy Transfer By Magnetic Tornadosupporting
confidence: 89%
See 4 more Smart Citations
“…The merged MC exhibits a longer lifetime of 1650 s (20,460 s < t < 22,110 s) in comparison to the average lifetime of individual MCs, which is typically 300-500 s. This finding is consistent with prior observations demonstrating that the lifetimes of magnetic bright points (MBPs), which serve as observational signatures of MCs, are prolonged during merging events as compared to the lifetimes of individual MBPs (Keys et al 2011). Given that MCs can impede local magnetoconvection and prevent the collapse of photospheric vortices (Finley et al 2022), it is plausible that the prolonged lifetimes of MCs observed in this study may facilitate the development of long-lived photospheric vortices, which can, in turn, give rise to magnetic tornadoes featuring the large-scale chromospheric swirls. The detailed analysis of the condition for magnetic tornadoes to form is a line for future research.…”
Section: Efficient Energy Transfer By Magnetic Tornadosupporting
confidence: 89%
“…to the corona. This finding is in line with previous investigations by Finley et al (2022). In this section, we further develop our discussion to address the underlying physical process for the enhancement of the coronal energy transport when the magnetic tornado is present, as compared to its absence.…”
Section: Efficient Energy Transfer By Magnetic Tornadosupporting
confidence: 86%
See 3 more Smart Citations